Automated Estimation and Tools to Extract Positions, Velocities, Breaks, and Seasonal Terms From Daily GNSS Measurements: Illuminating Nonlinear Salton Trough Deformation. Issue 7 (30th June 2020) - Heflin, Michael; Donnellan, Andrea; Parker, Jay; Lyzenga, Gregory; Moore, Angelyn; Ludwig, Lisa Grant; Rundle, John; Wang, Jun; Pierce, Marlon
Abstract: This paper describes the methods used to estimate positions, velocities, breaks, and seasonal terms from daily Global Navigation Satellite System (GNSS) measurements. Break detection and outlier removal have been automated so that decades of daily measurements from thousands of stations can be processed in a few hours. New measurements are added, and parameters are updated every week. Model parameters allow separation of interseismic, annual, coseismic, and postseismic signals. Tools available through GeoGateway (http://geo-gateway.org ) allow rapid visualization and analysis of these terms for results that can be subsetted in time or space. Results show highly variable and nonlinear motion for GPS stations in southern California. The variable motion is related to seasonal motions, distributed tectonic motion, earthquakes, and postseismic motions that can continue for years. In some areas results suggest that additional processes are responsible for the observed motions. In general, following earthquakes, stations return to their long‐term motions after 2–3 years, though some exceptions occur. The use of the tools shows nonlinear motion in the Salton Trough of southern California related to the 2010 M7.2 El Mayor‐Cucapah earthquake, 2012 Brawley earthquake swarm, and a creep event on the Superstition Hills fault in 2017. Key Points: Positions, velocities, breaks, and seasonal terms for thousands of GNSS stations are updated every week These results can be used to study interseismic plate motion, coseismic deformation, postseismic deformation, and seasonal variations The use of these tools shows highly variable nonlinear motion of GPS stations in southern California